Inpatient satisfaction with hospital services in Indonesia: A systematic review - Hapsari, Kanya; Sriatmi, Ayun; Kartini, Apoina (Interdisciplinary Social Studies, 2023)
Inpatient satisfaction is influenced by the quality of services provided by the hospital. The quality of service in question consists of Reliability, Assurance, tangibility, Empathy and Responsiveness. The aim of this research is to estimate and analyze the influence of the quality of inpatient services on patient satisfaction in hospitals. This research is a systematic review and metaanalysis research using the PRISMA diagram. Article searches were carried out based on the PICO Model eligibility criteria. P= InPatient; I = Good service quality; C= Poor Service Quality; O= Patient Satisfaction. Electronic literature was searched in 4 databases : Google Scholar, Research Gate, PubMed and Elsevier, for articles published on 2020-2023. With keywords including "service quality" AND "patient satisfaction" AND "Inpatient" AND "hospital" AND "cross sectional". Articles were analyzed using the PRISMA diagram and the Review Manager application. An article with a cross sectional study design that will be used as a source for meta-analysis of the influence of inpatient service quality on patient satisfaction in hospitals. The factors of service quality studied consisted of Reliability (reliability), Assurance (confidence), Tangible (physical appearance), Empathy (attention) and Responsiveness (responsiveness) which were proven to be able to influence patient satisfaction. The most dominant factors are Reliability, Empathy, and Responsiveness where the Sig. value is 0.000. Based on the research presented, it can be concluded that there is a significant relationship between service quality and patient satisfaction. All aspects of service quality, namely tangible, reliability, assurance, empathy, and responsiveness, are significantly related to patient satisfaction.